Study of Passenger Awareness and Satisfaction for IRCTC Catering Service and Dairy Products Offered during Train Journey - , Sudarshan M. Patel; , Mahendra D. Gurjar; , Krunal .C. Kamani; , Maulik C. Prajapati; , Ashish.K. Makwana (Archives of Current Research International, 2025)
This study investigates passenger awareness, buying behaviour and satisfaction related to IRCTC's catering services, with a specific focus on dairy product consumption during train journeys. Despite IRCTC's extensive food service network, there remains a lack of research on how well passengers are informed about available offerings, particularly newer options like e-catering and branded dairy products. Primary data were collected from 50 passengers across four major railway stations in Gujarat using structured questionnaires. Findings reveal that 96% of passengers were aware of IRCTC’s role in catering, and 70% had knowledge of e-catering services. Awareness of commonly available dairy items like flavoured milk (96%) and lassi (84%) was high, while only 26% and 16% recognized products like shrikhand and dairy sweets, respectively. Moreover, 58% of passengers reported always purchasing dairy products during their journey, with tea/coffee (84%) and flavoured milk (36%) being most preferred. The study highlights a strong engagement with core services but limited awareness and uptake of diverse dairy offerings. The results point to a clear opportunity for IRCTC to enhance communication strategies, improve product visibility, and strengthen dairy integration within its catering system to meet evolving passenger preferences.